The poet - Connelly, Michael, 1956- (new york : Warner Books, 2003)
A psychological thriller on a serial killer who hunts homicide detectives. The hero of the tale is Denver newspaper reporter Jack McEvoy whose brother, a detective, shoots himself. McEvoy investigates police suicides in other cities and discovers a sinister pattern: sex killings followed by the "suicide" of the detective on the case and a suicide note in the form of a poetic riddle. In this way McEvoy stumbles on the killer known to the FBI as The Poet, and teams up with a beautiful FBI agent to capture him. By the author of The Last Coyote.
All Ages.
UNCP 299590 - gift.
Keywords: Serial murders -- Fiction; Police murders -- Fiction; Journalists -- Fiction; Mystery fiction